Vasopressor Cumulative Dose Requirement and Risk of Early Death During Septic Shock: An Analysis From The EPISS Cohort. Issue 6 (June 2018) - Dargent, Auguste; Nguyen, Maxime; Fournel, Isabelle; Bourredjem, Abderrahmane; Charles, Pierre-Emmanuel; Quenot, Jean-Pierre
Abstract : ABSTRACT: Septic shock is the primary cause of death in intensive care units, with about 20% of patients dying in the first 3 days. To design future trials focused on early mortality, we require knowledge of early indicators that can detect patients at high risk of early death from refractory septic shock. The aim of this study was to assess whether the cumulative dose of vasopressors (CDV), calculated as the cumulative dose of epinephrine + norepinephrine, is a predictor of early death (within 72 h) attributable to refractory septic shock (EDASS). This substudy of the EPISS trial was based on 370 patients admitted to a French ICU for septic shock between 2009 and 2011. The area under the receiving operating characteristic curve was calculated for the CDV at 6, 12, 24, 36, and 48 h after vasopressor initiation, and a strategy to predict the risk of EDASS was built based on selected times and thresholds. Among the 370 patients included, 51 (14%) died within the first 72 h with 40 (11%) EDASS. A strategy in two steps (CDV ≥ 800 μg/kg at 6 h and/or CDV ≥ 2, 600 μg/kg at 24 h) was able to predict EDASS with sensitivity of 45%, specificity 97%, positive predictive value 78% and negative predictive value 94%. Overall, our results confirm that early death directly attributable to septic shock could be effectively predicted by the CDV in the first hours of treatment. These results will help to select patients eligible for innovative therapies aimed at improving early mortality in septic shock. Abstract : Supplemental Digital Content is available in the text